2019
DOI: 10.1109/tit.2019.2933520
|View full text |Cite
|
Sign up to set email alerts
|

Rank-Metric Codes Over Finite Principal Ideal Rings and Applications

Abstract: Several problems in algebraic geometry and coding theory over finite rings are modeled by systems of algebraic equations. Among these problems, we have the rank decoding problem, which is used in the construction of public-key cryptography. In 2004, Nechaev and Mikhailov proposed two methods for solving systems of polynomial equations over finite chain rings. These methods used solutions over the residual field to construct all solutions step by step. However, for some types of algebraic equations, one simply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(74 citation statements)
references
References 76 publications
1
73
0
Order By: Relevance
“…The simplified bound (14) in Theorem 5 coincides up to a constant with the bound by Gaborit et at. [10] in the case of a finite field (Galois ring with r = 1).…”
Section: Theorem 5 Let F Be Defined As In Defintion 2 Such That It Hasupporting
confidence: 74%
See 4 more Smart Citations
“…The simplified bound (14) in Theorem 5 coincides up to a constant with the bound by Gaborit et at. [10] in the case of a finite field (Galois ring with r = 1).…”
Section: Theorem 5 Let F Be Defined As In Defintion 2 Such That It Hasupporting
confidence: 74%
“…Network coding over certain finite rings was intensively studied in [ 7 , 11 ], motivated by works on nested-lattice-based network coding [ 8 , 18 , 26 , 28 ] which show that network coding over finite rings may result in more efficient physical-layer network coding schemes. Kamche et al [ 14 ] showed how lifted rank-metric codes over finite rings can be used for error correction in network coding. The result uses a similar approach as [ 23 ] to transformation the channel output into a rank-metric error-erasure decoding problem.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations